Analysis of The Use of Youtube (Children's Songs) in The Language Development of Children Aged 4-5 Years Darul Fikri Islamic Integral Kindergarten In Gading Cempaka District, Bengkulu City - Tamara, Shanny; Nirwan, Evi Silva (International Journal of Education, Information Technology, and Others, 2023)
The purpose of this study is: to find out how the use of YouTube (children's songs) in children's language development after 4-5 years in kindergarten integral isalm darul fikri. The type of research used is qualitative research with descriptive qualitative methods. Located at Darul Fikri Islamic Integral Kindergarten by looking at 2 research sources, namely 1 primary data source (educators) and secondary data sources (children) aged 4-5 years. The data collection techniques used are interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation (display data), conclusion drawing and verification (consclusing drawing / verification). The results of this study show that the Analysis of the Use of YouTube (children's songs) on language development in Islamic Integral Kindergarten darul Fikri is developing as expected. The shortcomings in this study are the appendix, which should be more complete documentation results in the study and does not include video results during observations and interviews at school. There are 3 indicators of language development of children aged 4-5ahun, namely: a). Understand language. b). Express language. c). Literacy. The implications of the study show that early childhood aged 4-5 years is expected to remain enthusiastic about learning independently at home to be able to further develop language development in children, education and parents are expected to pay more attention to providing lessons for their children so that the ability to understand children's language can develop, and researchers are expected to be more creative in conducting future research and subsequent researchers, in order to get maximum results.